The National Payment Systems Oversight Framework for the Maldives Monetary Authority - World Bank Group (World Bank, Washington, DC, 2019)
This report aims at assisting Maldives Monetary Authority (MMA) to establish an effective oversight framework to monitor the different payment and settlement systems, payment instruments and payment service providers in the Maldives. The framework for oversight is based on the Bank for International Settlement-International Organization of Securities Commissions (BIS-IOSCO) 24 principles and analyzing the payments development in the Maldives, while emphasizing the importance of overseeing several critical aspects of payment systems which are not within the radar of the present oversight unit. The BIS-IOSCO principles that are specifically on oversight function are set out in section one. Section two discusses the background and the present payment landscape, legal status, and critically review the present oversight arrangement by MMA, its mandate and suggest areas of improvement for an improved and effective oversight function. Section three outlines the present and future challenges for payment and settlement oversight unit (PSSOU) and provides guidelines to overcome some of the challenges. Section four sets out recommendations to be adopted by PSSOU and section five articulates the most urgent tasks that should be undertaken by PSSOU and MMA to ensure an effective oversight on the national payments system (NPS) in the Maldives.